Proposed content in health instruction for third year high school - Mendoza, Asuncion J. 1933- ([Quezon City s.n.], 1968)
The documentary analysis method is used in the study in an attempt to propose the content for health instruction based on established needs and interests of the third year high school students. The study revealed that the students' health needs and health interests are on the following areas: Keeping Fit, Group Health, Causes of Diseases, Protection Against Diseases, Structure and Function of the Body, Dental Health, Good Eating Habits, Selection and Composition of Foods, Stimulants and Narcotics, Rest, Sleep and Relaxation, Personal Appearance, Personality Development, Social Health, and Safety.
Thesis (M.Ed.)--University of the Philippines
Keywords: Health education -- Curricula